2016
DOI: 10.1016/j.micinf.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

IRE1α mediates PKR activation in response to Chlamydia trachomatis infection

Abstract: Protein kinase RNA activated (PKR) is a crucial mediator of anti-viral responses but is reported to be activated by multiple non-viral stimuli. However, mechanisms underlying PKR activation, particularly in response to bacterial infection, remain poorly understood. We have investigated mechanisms of PKR activation in human primary monocyte-derived dendritic cells in response to infection by Chlamydia trachomatis. Infection resulted in potent activation of PKR that was dependent on TLR4 and MyD88 signalling. NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
(62 reference statements)
2
30
0
Order By: Relevance
“…This is supported by multiple pieces of evidence, including, splicing of IRE1α downstream target XBP1 and the attenuation of an inflammatory response and severe disease pathology by pharmacological inhibition of IRE1α. These observations corroborate with studies where activation of IRE1-XBP1-mediated ER stress has also been reported via various intracellular pathogens such as Chlamydia trachomatis, 55 Brucella abortus, 56 and Francisella tularensis. 27 However, some other bacterial species and their toxins such as subtilase toxin produced by Escherichia coli, 57 and listeriolysin O, produced by Listeria monocytogenes 58 have been shown to activate other arms of the UPR as well.…”
Section: Discussionsupporting
confidence: 91%
“…This is supported by multiple pieces of evidence, including, splicing of IRE1α downstream target XBP1 and the attenuation of an inflammatory response and severe disease pathology by pharmacological inhibition of IRE1α. These observations corroborate with studies where activation of IRE1-XBP1-mediated ER stress has also been reported via various intracellular pathogens such as Chlamydia trachomatis, 55 Brucella abortus, 56 and Francisella tularensis. 27 However, some other bacterial species and their toxins such as subtilase toxin produced by Escherichia coli, 57 and listeriolysin O, produced by Listeria monocytogenes 58 have been shown to activate other arms of the UPR as well.…”
Section: Discussionsupporting
confidence: 91%
“…The obligate intracellular pathogen Chlamydia induces the UPR by upregulating BiP (44,45). Chlamydia infection also induces TLR4/IRE1-mediated activation of PKR, which enhances IFN-β production (46). Brucella abortus localizes to the ER by transforming its fine reticular pattern into a thicker tubular structure (47).…”
Section: Bacterial Infection and Er Stressmentioning
confidence: 99%
“…One group reported that persistent (non-productive) Chlamydia infection induced transient BiP upregulation and eIF2α phosphorylation but not ATF6 cleavage or XBP1 splicing ( 179 ). However, in another study, Chlamydia stimulated “robust” IRE1 activation and XBP1 splicing, and induced CHOP in a GCN2-dependent manner ( 180 ). Legionella actively inhibited XBP1 splicing via bacterial translation elongation inhibitors ( 181 ).…”
Section: Implications For Bacterial Infectionsmentioning
confidence: 99%
“…Chlamydia also induced PKR-dependent IFN-β through a mechanism requiring TLR4 and IRE1 RNase activity. Interestingly, this TLR4 activity may limit CHOP induction, stressing the importance of the multiple innate immune and ER stress inputs that impact cytokine production during infection ( 180 ). XBP1 deficiency significantly decreased TLR2-dependent TNF-α and IL-6 responses to Francisella in vitro .…”
Section: Implications For Bacterial Infectionsmentioning
confidence: 99%